STUDY ABOUT KENDUHAI SKO TRADITIONAL CLOTHING DESIGN IN SUNGAI PENUH CITY JAMBI PROVINCE - Nabila Aprimania; Yuliarma Yuliarma (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
This study aims to describe the design characteristics, complements, accessories, how to use traditional clothing, and analyze the meaning contained in Kenduhai Sko traditional clothing in Sungai Penuh City. This research method is descriptive qualitative. Data were collected using observation, interview, and documentation techniques. Data analysis used interactive analysis collection techniques related to the subject matter studied. The results of the study 1) Depati and Rio's traditional clothes consist of a kuhong shirt and long pants, using an H silhouette. Black Japan drill material; 2) Complementary clothing, namely rawo shawl, lita, and lipak; 3) Clothing accessories, namely keris, dasinul and kampeng for Depati and sticks for Rio; 4) How to wear traditional clothes for Depati using a kuhong shirt, long pants, straight-shaped lipak cloth, a rawo scarf, finally insert a keris that has been tied with dasinul and kampeng, then use lita. For Rio, he uses a kuhong shirt, long pants, lipak cloth, rawo shawl, uses a lita and holds a stick; 5) The aesthetic meaning of the kuhong shirt and pants as an identity and the value of modesty, the black color symbolizes power, the rawo shawl means self-control, the lipak cloth means protecting, lita as a symbol of wisdom, the keris which reflects authority, kampeng which functions to store cigarettes, Dasinul means control his power, the stick is to protect.